2020
DOI: 10.1101/2020.05.26.081083
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell states beyond transcriptomics: integrating structural organization and gene expression in hiPSC-derived cardiomyocytes

Abstract: SummaryWe present a quantitative co-analysis of RNA abundance and sarcomere organization in single cells and an integrated framework to predict subcellular organization states from gene expression. We used human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes expressing mEGFP-tagged alpha-actinin-2 to develop quantitative image analysis tools for systematic and automated classification of subcellular organization. This captured a wide range of sarcomeric organization states within cell populations… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 134 publications
0
22
0
Order By: Relevance
“…In our previous study, we found that, similar to mouse PSC-CMs, human PSC-CMs appear to have a maturation state similar to fetal CMs and appear arrested at the onset of perinatal maturation (5). Here, we focused on four published datasets of CMs generated from induced PSCs - Friedman, Nguyen, and Lukowski et al (38) (FNL); Churko et al (39) (C); Gerbin, Grancharova, Donovan-Maye, and Hendershott et al (40) (GGDH); and Ruan and Liao et al (41) (RL). We initially aimed to perform trajectory reconstruction with Monocle 3 as done with the mouse PSC-CMs.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we found that, similar to mouse PSC-CMs, human PSC-CMs appear to have a maturation state similar to fetal CMs and appear arrested at the onset of perinatal maturation (5). Here, we focused on four published datasets of CMs generated from induced PSCs - Friedman, Nguyen, and Lukowski et al (38) (FNL); Churko et al (39) (C); Gerbin, Grancharova, Donovan-Maye, and Hendershott et al (40) (GGDH); and Ruan and Liao et al (41) (RL). We initially aimed to perform trajectory reconstruction with Monocle 3 as done with the mouse PSC-CMs.…”
Section: Resultsmentioning
confidence: 99%
“…Our studies add a new dimension to these analyses by incorporating the spatial organization of cell structures, that is, where and when these parts come together in space and time to drive that function. Our approach relies on the well-established tight linkage between 3D cell organization and cell function, aspiring to use this to identify cell types and states from images, and relate them to single cell gene expression profiles (Gerbin et al, 2020). These approaches were built with live cell imaging in mind and thus are poised to incorporate dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches were built with live cell imaging in mind and thus are poised to incorporate dynamics. Recently, studies combining quantitative measures of sarcomere organization with gene expression in the same individual cardiomyocytes demonstrates the importance of incorporating the spatial cell organization metrics for a more complete classification of cell states (Gerbin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that we do not see entropy score as the end-all for maturation quantification. In addition to potential discrepancies between transcript and protein level expression (53), the mature cellular phenotype encompasses numerous functional parameters that may be only partially captured at the transcriptomic level (54). We envision entropy score as complementing existing celltype-specific functional assays to advance a more complete assessment of single cell maturation status.…”
Section: Discussionmentioning
confidence: 99%